Kehadiran Roh Kudus dalam Pelayanan: Rahasia Khotbah Yang Diurapi - Norina Halawa; Yesa Cinta; Etni Grace Andi Yusuf (Sekolah Tinggi Teologi Berita Hidup, 2026)
The presence of the Holy Spirit in Christian ministry, especially in the context of anointed preaching, has a profound and transformational role. This study aims to explore how the Holy Spirit influences the quality and effectiveness of preaching in the context of the contemporary church. Through a descriptive qualitative approach, this study examines the perceptions and experiences of preachers and congregations regarding the anointing of the Holy Spirit in preaching. The results show that the anointing of the Holy Spirit strengthens the power of the proclamation of God's Word, increases the understanding and acceptance of the congregation, and brings about significant spiritual change. This study also identifies the variability of the anointing experience, which is influenced by the preacher's personal factors, spiritual preparation, and dependence on the Holy Spirit. In conclusion, this study confirms that the anointing of the Holy Spirit is a critical factor in effective preaching ministry, which requires full dependence on divine power to influence and change the lives of the congregation. Through anointed preaching, the church can realize living and powerful teaching, which influences and shapes Christians to become more mature in faith and love.